Optimizing Texture and Aroma in Fruit Leather: Effects of Jackfruit–Soursop Ratios and Flour Type - Sondjana Ali, Suganda; Masatip, Anwari; Ab, Ahmad; Hidayat, Nova Maulidian; Komariah, Nur (Politeknik Pariwisata Makassar, Indonesia, 2026)
This study investigated the systemic effects of varying jackfruit (Artocarpus heterophyllus) and soursop (Annona muricata) ratios, combined with distinct flour types, on the sensory and physical characteristics of fruit leather. Jackfruit and soursop purees were blended at ratios of 80:20, 50:50, and 30:70, then formulated with 30 g of wheat, tapioca, or rice flour as stabilizing binding agents. The mixtures were dehydrated at a controlled temperature of 60 °C. Sensory evaluation was conducted using a structured hedonic scale to assess the acceptability of flavor, color, aroma, and texture. Statistical analysis using ANOVA and DMRT (α = 0.05) demonstrated that both the fruit ratio and binder type significantly influenced the product’s quality attributes. The 80:20 jackfruit-soursop ratio with wheat flour produced the most preferred flavor (3.33) and color (3.40). In terms of aroma, the 30:70 ratio exhibited the most balanced profile across all flour types. Notably, the 80:20 ratio with rice flour achieved the highest texture preference (3.00), providing superior structural integrity and mouthfeel compared to tapioca and wheat. However, at the 30:70 ratio, wheat flour emerged as the optimal binder for texture (2.73). Consequently, this research highlights the potential of optimizing tropical fruit formulations to develop high-quality functional snacks. These findings suggest that rice flour is ideal for fiber-rich jackfruit leather, while wheat flour is more suitable for moisture-rich soursop blends